EKSPLORASI WISATA ALAM NAGARI BATU BAJANJANG MELALUI FILM DOKUMENTER - ULFA FAUZIAH, Dr. Syafwandi, M.Sn., Drs. Ariusmedi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this article to intoduce Nagari Batu Bajanjang has a high natural tourism sector. Nagari Batu Bajanjang has many natural attractions that have not been previously published and documented. These natural tourism objects are include of Air Panas Telaga Zam-zam, Gabuo Indah, Tabek Ilang Lanyek, Puncak Batu Gadang Sibeloh and Air Terjun Surau Kasiak. The lack of information and promotion of natural tourism is also one of the causes many tourist do not know the tourist attractrions in this region. In this design, author chooses audio visual media in Documentary Film forms. The purpose of designing this documentary film is to get an effective, objejctive and communicative DKV design so that the target audience can find out about the natural tourism attractions in Nagari Batu Bajanjang. The design methodology of this documentary film for The Natural Tourism of Nagari Batu Bajanjang uses teh 5W+1H (what, who, when, where, why and how) analysis approach. The design of this documentary film has several supporting media included by posters, stickers, T-Shirt, bags, CD covers, CD labels, mugs and backdrops.Key Words : Documentary Film, The Natural Tourism of Nagari Batu Bajanjang